2012
DOI: 10.4049/jimmunol.1201892
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating γδ T Lymphocytes Predict Clinical Outcome in Human Breast Cancer

Abstract: Understanding and dissecting the role of different subsets of regulatory tumor-infiltrating T lymphocytes (TILs) in the immunopathogenesis of individual cancer is a challenge for anti-tumor immunotherapy. High levels of γδ regulatory T (Treg) cells have been discovered in the breast TILs. However, the clinical relevance of these intra-tumoral γδ T cells is unknown. In this study, γδ T cell populations were analyzed by performing immunohistochemical staining in primary breast cancer tissues from patients with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
160
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(177 citation statements)
references
References 48 publications
10
160
0
Order By: Relevance
“…Moreover, Vd1 cells were the dominant tumor-infiltrating T cell population found in a collection of 74 primary cutaneous melanomas (19). However, other studies by Peng and colleagues (18) detected poor infiltration of Vd1 T cells, as well as total gd T cells (50), in melanoma biopsy specimens. By contrast, gd T cells, and Vd1 cells in particular, were abundant in breast and prostate tumors.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Vd1 cells were the dominant tumor-infiltrating T cell population found in a collection of 74 primary cutaneous melanomas (19). However, other studies by Peng and colleagues (18) detected poor infiltration of Vd1 T cells, as well as total gd T cells (50), in melanoma biopsy specimens. By contrast, gd T cells, and Vd1 cells in particular, were abundant in breast and prostate tumors.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, γδ T cells represented the most significant independent prognostic factor for assessing severity of breast cancer (16). Similarly, a recent report on colorectal cancer showed a positive correlation between clinopathological parameters and the infiltration of γδ T cells specifically producing interleukin-17 (IL-17) (17).…”
Section: Gamma-delta T Cells | Tumor Immunologymentioning
confidence: 94%
“…Despite these highly promising reports, a clinical study on breast cancer tissue revealed a surprising inverse correlation between infiltrating γδ T cells and overall patient survival (16). In fact, γδ T cells represented the most significant independent prognostic factor for assessing severity of breast cancer (16).…”
Section: Gamma-delta T Cells | Tumor Immunologymentioning
confidence: 99%
“…47 Their continuance is of specific significance early after haematopoietic SCT when patients, still immunocompromised, suffer from a high risk of lymphoproliferative disorders 48 and relapse of the underlaying disease, as γδT cells can suppress B-cell expansion, 49 regulate T-cell leukaemia and exert potent antitumoural activity. [50][51][52][53][54][55][56] Furthermore, the key role of γδT cells in primary immune responses is undisputed in CMV, HSV-1 and Candida albicans infections, pathogens that are frequent after transplantation. [57][58][59] In addition, γδT cells are crucial modulators of immune responses and decisive in the induction and maintenance of tolerance in various physiological settings [60][61][62][63] and can directly promote allograft survival.…”
Section: Discussionmentioning
confidence: 99%